2012
DOI: 10.5858/arpa.2011-0370-oa
|View full text |Cite
|
Sign up to set email alerts
|

Structured Electronic Template for Histopathology Reporting on Colorectal Carcinoma Resections: Five-Year Follow-up Shows Sustainable Long-Term Quality Improvement

Abstract: Objective.-To investigate use and long-term effect of this structured template in one of the first laboratories implementing the template for routine diagnostic work.Design.-All histopathology reports (n = 123) in the 1-year period prior to implementation were evaluated with respect to presence of key parameters. Likewise, all histopathology reports (n = 1186) in the 5-year period after implementation were evaluated with respect to template use and presence of key parameters.Results.-The electronic template ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…As previously mentioned, there is an abundance of evidence that mandating and requiring a specific list of elements for inclusion in synoptic reporting, along with the provision of a checklist of those items, can successfully improve the completeness of reports. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] There are also published data concerning the accuracy of the data included in a synoptic report. Specifically, the words no and not are rarely but consistently left off of reports reducing accuracy, and ensuring that the phrases in the checklist contain as few of these elements as possible improves accuracy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, there is an abundance of evidence that mandating and requiring a specific list of elements for inclusion in synoptic reporting, along with the provision of a checklist of those items, can successfully improve the completeness of reports. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] There are also published data concerning the accuracy of the data included in a synoptic report. Specifically, the words no and not are rarely but consistently left off of reports reducing accuracy, and ensuring that the phrases in the checklist contain as few of these elements as possible improves accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…The CAP specifically requires that each element in a synoptic report be reported in a required data element (RDE) pair consisting of the element and the corresponding response (CAP Laboratory Accreditation Process Checklist question ANP.12385). 1 While there are significant data supporting the use of checklists in general, 2-14 and their use to improve the completeness of surgical pathology reporting specifically, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] there are much fewer data concerning the significance of the specific formats. Valenstein 34 examined structured reporting and focused on diagnostic headlines, white space, standardized layout, continuity over time, and reduction of clutter but provided few data addressing the specific formats.…”
mentioning
confidence: 99%
“…First, the use of synoptic reporting, a protocol or a template has been proven superior in ensuring that key parameters are reported [54,55,56,57,58,59]. These are parameters that are essential in planning further treatment and follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The histopathology report has traditionally been in a free text (narrative) format. Many studies have however shown that the use of checklists or structured text elements improve the quality of the histopathology report with respect to the presence of key information deemed important for patient treatment [1-3]. With the introduction of electronic health records, structured histopathology reporting can be done using predefined drop down menus with automated coding.…”
Section: Introductionmentioning
confidence: 99%